2016
DOI: 10.1016/j.scitotenv.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radionuclide contamination on leaf litter decomposition in the Chernobyl exclusion zone

Abstract: The effects of radioactive contamination on ecosystem processes such as litter decomposition remain largely unknown. Because radionuclides accumulated in soil and plant biomass can be harmful for organisms, the functioning of ecosystems may be altered by radioactive contamination. Here, we tested the hypothesis that decomposition is impaired by increasing levels of radioactivity in the environment by exposing uncontaminated leaf litter from silver birch and black alder at (i) eleven distant forest sites differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…In the present study, adult zebrafish were exposed to 4 dose rates (0,0.5,5,137 Cs gamma radiation) over 10 d. The dose rates were higher than those in "hot spots" measured in freshwater ecosystems around Chernobyl, Pryp'yat', Ukraine (<0.2 mGy h -1 ; Lecomte-Pradines et al 2014;Bonzom et al 2016;Fuller et al 2018;Lerebours et al 2018). Reproduction was initiated, and the progeny were then exposed or not to the same dose rates over 96 to 120 h. The objectives of the present study were to evaluate 1) adult reproductive performance, 2) the effects in the progeny of irradiated parents, and 3) the responses at the molecular and organism levels.…”
Section: Introductionmentioning
confidence: 79%
“…In the present study, adult zebrafish were exposed to 4 dose rates (0,0.5,5,137 Cs gamma radiation) over 10 d. The dose rates were higher than those in "hot spots" measured in freshwater ecosystems around Chernobyl, Pryp'yat', Ukraine (<0.2 mGy h -1 ; Lecomte-Pradines et al 2014;Bonzom et al 2016;Fuller et al 2018;Lerebours et al 2018). Reproduction was initiated, and the progeny were then exposed or not to the same dose rates over 96 to 120 h. The objectives of the present study were to evaluate 1) adult reproductive performance, 2) the effects in the progeny of irradiated parents, and 3) the responses at the molecular and organism levels.…”
Section: Introductionmentioning
confidence: 79%
“…Forest litter accumulates in contaminated areas (including the Red Forest) within the CEZ [ 79 ], potentially increasing available microbial niche space from which bank voles SK microbiome is sourced, given that bank voles inhabit burrows and move about the leaf litter. Curiously, accumulation of forest litter in contaminated areas within the CEZ implies impaired function of microbial decomposers and/or soil invertebrates [ 79 ], but see also [ 80 ]. As such, high SK microbiome diversity within the CEZ (and by implication high microbial diversity in the surrounding environment) does not appear to be associated with a healthy ecosystem function [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported no substantial effects of radiation on wildlife in the Chernobyl Exclusion Zone (CEZ) (e.g. Chesser and Baker, 2006;Deryabina et al, 2015;Murphy et al, 2011;Bonzom et al, 2016). Conversely, others report significant impacts of radiation on wildlife at extremely low dose rates.…”
Section: Introductionmentioning
confidence: 99%